Quantification of Serial Cerebral Blood Flow in Acute Stroke Using Arterial Spin Labeling. Issue 1 (January 2017) - Harston, George W.J.; Okell, Thomas W.; Sheerin, Fintan; Schulz, Ursula; Mathieson, Phil; Reckless, Ian; Shah, Kunal; Ford, Gary A.; Chappell, Michael A.; Jezzard, Peter; Kennedy, James
Abstract : Background and Purpose—: Perfusion-weighted imaging is used to select patients with acute ischemic stroke for intervention, but knowledge of cerebral perfusion can also inform the understanding of ischemic injury. Arterial spin labeling allows repeated measurement of absolute cerebral blood flow (CBF) without the need for exogenous contrast. The aim of this study was to explore the relationship between dynamic CBF and tissue outcome in the month after stroke onset. Methods—: Patients with nonlacunar ischemic stroke underwent ⩽5 repeated magnetic resonance imaging scans at presentation, 2 hours, 1 day, 1 week, and 1 month. Imaging included vessel-encoded pseudocontinuous arterial spin labeling using multiple postlabeling delays to quantify CBF in gray matter regions of interest. Receiver–operator characteristic curves were used to predict tissue outcome using CBF. Repeatability was assessed in 6 healthy volunteers and compared with contralateral regions of patients. Diffusion-weighted and T2-weighted fluid attenuated inversion recovery imaging were used to define tissue outcome. Results—: Forty patients were included. In contralateral regions of patients, there was significant variation of CBF between individuals, but not between scan times (mean±SD: 53±42 mL/100 g/min). Within ischemic regions, mean CBF was lowest in ischemic core (17±23 mL/100 g/min), followed by regions of early (21±26 mL/100 g/min) and late infarct growth (25±35 mL/100 g/min; ANOVA P <0.0001). Between patients, there was marked overlap in presenting and serial CBF values. Conclusions—: Knowledge of perfusion dynamics partially explained tissue fate. Factors such as metabolism and tissue susceptibility are also likely to influence tissue outcome. Abstract : Supplemental Digital Content is available in the text.